ADAPTIVE OPTICAL SYSTEMS LIGHTING EQUIPMENT VEHICLES - S. P. Sernov; D. V. Balokhonov; T. V. Kolontaeva; A. V. Zhuravok (Приборы и методы измерений, 2015)
This article describes the main principles of implementation of modern adaptive signal lighting equipment of vehicles, provides an analysis of optical systems are used, the necessity of the use of LEDs. We present the design of adaptive optical system, rear combination LED lamp of a vehicle with several levels of intensity, we discuss the algorithm of its work in different modes.